2020
DOI: 10.1080/23322039.2020.1734324
|View full text |Cite
|
Sign up to set email alerts
|

Funding liquidity and bank lending

Abstract: We investigate how funding liquidity affects the bank lending using a large sample of US bank holding companies. We document a consistent evidence of a lower loan growth for banks that rely more on deposits. The quantile regressions which dissect the lending behavior of banks at the right tail of loan growth distribution point out the leveraged effect of funding liquidity is larger in high-loangrowth banks. The negative effects of funding liquidity on lending seem to be clearer before the crisis and especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This indicates that state-owned banks were more countercyclical in their lending during the COVID-19 pandemic than private banks. This result is also closely related to Tran (2020), Bertay et al. (2015) and Brei and Schclarek (2013).…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…This indicates that state-owned banks were more countercyclical in their lending during the COVID-19 pandemic than private banks. This result is also closely related to Tran (2020), Bertay et al. (2015) and Brei and Schclarek (2013).…”
Section: Resultssupporting
confidence: 63%
“…Aldasoro et al (2020) noted that COVID-19 produces a complex and varied set of consequences for banks and threatens the banking system's stability. Many studies showed different impacts of the global financial crisis depending on government-owned and private banks (Bertay et al, 2015;Brei and Schclarek, 2013;Cortes et al, 2019;Gambacorta et al, 2011;Tran, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In finance literature, there are several definitions that are predominantly used to distinguish funding liquidity which relates to obtaining financing from market liquidity as a measure of market depth. As the term suggests, funding liquidity relates to the availability of credit in the market (Tran, 2020). Market liquidity on the other hand plays an important role in financial market analysis due to the perceived notion that fundamentals are usually based on liquidity drivers (Warsh, 2007).…”
Section: Introductionmentioning
confidence: 99%